Object Detection Using a Compact Single Resonant Antenna for Microwave Imaging Applications - Helda Khader, Amal Jaber, Yanal S. Faouri (International Journal of Advanced Science and Technology, 2020)
A single band antenna has been utilized for sensing purposes is proposed. Different parameters related to the object have been considered such as Distance, location in space, size, permittivity and conductivity. The antenna characteristics monitored are reflection coefficient, gain, pattern, and others and their data are tabulated to identify the detected object. High-Frequency Structure Simulator (HFSS) has been used to simulate and interpret the different antenna parameters. Results showed that any change in the object geometry or properties will reflect on antenna parameters.